Numerical Simulation of Flow through a Circular Cylinder with 2 Rotating Controllers having Crucial-Shape Placed behind - Phan, Duc Huynh; Nguyen, Tran Ba Dinh (Old Journal, 2020)
When a fluid with coefficient Re ≥ 47 flows through a certain structure, they will interact with each other. This can cause oscillation and lead to the destruction of a structure due to the flow effects. One of the techniques to reduce structural vibration is to use sub-systems to change the flow structure. In this research, the immersed boundary method is applied to investigate the effect of controlling flow through a circular cylinder by placing two rotating controllers with crucial shape. The results showed that the lift force and drag force acting on the circular cylinder are significantly decreased. Besides, the influence from the placing position of 2 crucial to the drag coefficient and lift coefficient is also investigated. From the results, it can be concluded that 2 rotating crucial can eliminate the vortex and stabilize the flow if their position and rotating speed are reasonable.